2021
DOI: 10.1111/jrh.12638
|View full text |Cite
|
Sign up to set email alerts
|

Mental health at the COVID‐19 frontline: An assessment of distress, fear, and coping among staff and attendees at screening clinics of rural/regional settings of Victoria, Australia

Abstract: Purpose Research examining psychological well‐being associated with COVID‐19 in rural/regional Australia is limited. This study aimed to assess the extent of psychological distress, fear of COVID‐19, and coping strategies among the attendees in COVID‐19 screening clinics at 2 rural Victorian settings. Methods A cross‐sectional study was conducted during July 2020 to February 2021 inclusive. Participants were invited to fill in an online questionnaire. Kessler Psychological Distress Scale (K‐10), Fear of COVID‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Similar results were reported in a large international sample during COVID-19 [5]. An Australian study also found that individuals with higher quali cations (i.e., bachelor's degree) reported increased normal to high resilience scores [42]. This was attributed to enhanced critical thinking and problemsolving skills leading to the use of more adaptive coping strategies.…”
Section: Copingsupporting
confidence: 79%
“…Similar results were reported in a large international sample during COVID-19 [5]. An Australian study also found that individuals with higher quali cations (i.e., bachelor's degree) reported increased normal to high resilience scores [42]. This was attributed to enhanced critical thinking and problemsolving skills leading to the use of more adaptive coping strategies.…”
Section: Copingsupporting
confidence: 79%
“…In the rural healthcare setting where the current study was based, a higher proportion of staff was likely to have a mental health issue at Time 2 during COVID-19 compared to Time 1 (though not statistically significant). A recent study of 702 attendees at south west Victoria COVID-19 screening clinics showed 22% of attendees experienced high to very high levels of psychological distress using the Kessler 10 ( Rahman et al, 2022 ). Of particular note is that 43% of these attendees were essential workers ( Rahman et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 702 attendees at south west Victoria COVID-19 screening clinics showed 22% of attendees experienced high to very high levels of psychological distress using the Kessler 10 ( Rahman et al, 2022 ). Of particular note is that 43% of these attendees were essential workers ( Rahman et al, 2022 ). Other studies in Australian metropolitan health services have also shown an increases in mental health symptoms and psychological distress associated with the COVID-19 pandemic in healthcare workers ( Dobson et al, 2021 ; Holton et al, 2021a , 2021b ; Smallwood et al, 2021 ); however, direct comparison to the current study isn't possible due to the different psychological distress tools utilised.…”
Section: Discussionmentioning
confidence: 99%
“…Stress management is crucial for the well-being of emergency physicians, who face increasing distress, with burnout rates reaching alarming levels globally [7,[29][30][31]. Excessive stress not only jeopardizes mental health but also compromises the quality of patient care [32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%